Characteristics of post-overdose public health-public safety outreach in Massachusetts. (1st February 2021) - Formica, Scott W.; Waye, Katherine M.; Benintendi, Allyn O.; Yan, Shapei; Bagley, Sarah M.; Beletsky, Leo; Carroll, Jennifer J.; Xuan, Ziming; Rosenbloom, David; Apsler, Robert; Green, Traci C.; Hunter, Allie; et al.
Highlights: Post-overdose outreach has emerged as a way to mitigate future overdose risk. We identified 157 programs in Massachusetts with a two-part cross-sectional survey. Overdose survivors were identified almost always via police-supplied 911 call data. Outreach teams usually consisted of police, recovery coaches, or harm reductionists. Teams provided or made referrals to OD prevention, treatment, and recovery support. Abstract: Background: As a response to mounting overdose fatalities, cross-agency outreach efforts have emerged to reduce future risk among overdose survivors. We aimed to characterize such programs in Massachusetts, with focus on team composition, approach, services provided, and funding. Methods: We conducted a two-phase cross-sectional survey of public health and safety providers in Massachusetts. Providers in all 351 municipalities received a screening survey. Those with programs received a second, detailed survey. We analyzed responses using descriptive statistics. Results: As of July 2019, 44 % (156/351) of Massachusetts municipalities reported post-overdose outreach programs, with 75 % (104/138) formed between 2016−2019. Teams conducted home-based outreach 1–3 days following overdose events. Police departments typically supplied location information on overdose events (99 %, 136/138) and commonly participated in outreach visits (86 %, 118/138) alongside public health personnel, usually from community-based organizations. Teams provided or made referrals to services including inpatient addiction treatment, recovery support, outpatient medication, overdose prevention education, and naloxone. Some programs deployed law enforcement tools, including pre-visit warrant queries (57 %, 79/138), which occasionally led to arrest (11 %, 9/79). Many programs (81 %, 112/138) assisted families with involuntary commitment to treatment – although this was usually considered an option of last resort. Most programs were grant-funded (76 %, 104/136) and engaged in cross-municipal collaboration (94 %, 130/138). Conclusions: Post-overdose outreach programs have expanded, typically as collaborations between police and public health. Further research is needed to better understand the implications of involving police and to determine best practices for increasing engagement in treatment and harm reduction services and reduce subsequent overdose.